THE EFFECT OF SCHOOL PRINCIPAL'S ACADEMIC SUPERVISION, SELF-EFFICACY, AND ORGANIZATIONAL CULTURE ON THE PERFORMANCE OF VOCATIONAL SCHOOL (SMK) TEACHERS IN THE THIRD PRIVATE GROUP IN THE PAMULANG DISTRICT - Suprihatin, Suprihatin; Anwar, Saiful; Zubaidah, Siti (Komunitas Manajemen Kompetitif, 2025)
This study examines the effects of principal academic supervision, teacher self-efficacy, and organizational culture on teacher performance in private vocational schools in South Tangerang, Indonesia. Using a quantitative associative design, 118 teachers were sampled from 11 schools. Data were collected through validated questionnaires and analyzed using multiple linear regression and path analysis. Results show that academic supervision has the strongest direct effect on teacher performance (β = 0.801, p < 0.05), followed by organizational culture (β = 0.615, p < 0.05) and self-efficacy (β = 0.438, p < 0.05). Academic supervision and self-efficacy also positively influence organizational culture (β = 0.305 and 0.174, p < 0.05). However, indirect effects through organizational culture (0.188 and 0.107) are smaller than direct effects, indicating that organizational culture acts more as a supportive factor than a mediator. The study highlights the importance of strengthening supervision and self-efficacy while fostering a positive organizational culture to enhance teacher performance. The findings provide practical guidance for school leaders and policymakers to improve professional development and school effectiveness.